Challenges in Diagnostic and Management of Nephritic Syndrome in Diabetic Nephropathy Patient: a Case Report - Novitasari, Adinda Dian; Samsu, Nur (Clinical and Research Journal in Internal Medicine, 2021)
The clinical presentation of patients with acute glomerulonephritis (GN) varies widely, from asymptomatic to clinical presentations of acute kidney injury (AKI), edema, and hypertension. Diagnosis of GN in patients with diabetic nephropathy (DN) is a challenge due to pre-existing edema, hypertension, and decreased renal function. Likewise in terms of management of steroid immunosuppressants related to blood sugar regulation. It has been reported that 35-year-old male patients with diabetes mellitus (DM) with DN whose kidney function deteriorated rapidly. The patient complained of cola-red urine and decreased urine volume the day before admission. Physical examination showed blood pressure of 160/95 mmHg, bilateral leg edema, active chronic ulcer in the left lower leg, hemoglobin level was 8.7 g / dl, leukocytes 17.400 / ul, serum urea level 96 mg / dl, serum creatinine level 7.01 mg / dl, ASTO titer + 800 IU / ml, macroscopic hematuria, and albuminuria +4 on urinalysis. Ultrasonography revealed enlarged kidney size and signs of acute renal inflammation. Based on these data the patient was diagnosed clinically as rapidly progressive GN due to post-infectious GN. The patient received 3 days of pulse methyl prednisolone therapy continued orally, blood sugar regulation with insulin, RAS blockers, intravenous antibiotics and ulcer debridement. After 1 week of therapy, clinical and laboratory improvements were found and at the next follow-up renal function returned to baseline about 2 weeks later.